Egestion rates of the telescope snail Telescopium telescopium (Linne). - Franco, Eileen Bravo
Egestion rates of Telescopium telescopium in relation to size were studied by first acclimating the ten samples for every size batch (24 hours) and feeding them (14 hours) with the organic content in the sediment, Shell lenghts ranged from 30-74.5 mm and based on this, five size classes were established (i.e. 30-39.99 mm, 40-49.99 mm, 50-59.99 mm, 60-69.99 mm and 70-74.50 mm). The snails were placed in beakers with seawater and the egestion time for every sample was observed for a duration of 15 minutes. Based on the amount of fecal material egested (mg) through time (min), the egestion rates from the slope of the linear regressions were determined. Water parameters like temperature, salinity and pH together with the organic matter content of the sediment were also measured. Fastest egestion rate was observed at sizes between 60-69.99 mm. The rates were not observed to vary directly or inversely with size. On the other hand, a high negative correlation was obtained in size class 40-49.99 mm due to the more uniform trend of decrease of weight over time. Further studies should investigate the effect of variation in meal size and food particle size on egestion rate. Other direct methods in quantifying egestion rate like nitrogen balance method and radioisotope method may be also examined